2012
DOI: 10.3390/su4071619
|View full text |Cite
|
Sign up to set email alerts
|

In Transition towards Sustainability: Bridging the Business and Education Sectors of Regional Centre of Expertise Greater Sendai Using Education for Sustainable Development-Based Social Learning

Abstract: This article discusses a business-school collaborative learning partnership in the Regional Centre of Expertise (RCE) on Education for Sustainable Development (ESD) in Greater Sendai. This partnership is further linked to a broader context of multi-stakeholder public participation in the RCE that was set up to advance the ESD agenda in the region. The authors propose a conceptual framework for multi-stakeholder, ESD-based social learning within the RCE with the aim of enabling the creation of a sustainability-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In line with the call for promoting DESD in higher education, some university programs placed their emphasis on active learning and development of skills to solve problems that students would face in the real world [28][29][30]. The university's role in regional sustainability, on the other hand, includes educating citizens to foster volunteers who can contribute to developing sustainability in local communities [31] and developing partnerships for SD initiatives between universities and other local stakeholders [32], which have been manifested by efforts to set up Regional Centers of Expertise on ESD around the world [33,34]. Although not explicitly stated, those activities overlap with the engagement of scholarship.…”
Section: Universities' Roles In Education For Sustainable Developmentmentioning
confidence: 99%
“…In line with the call for promoting DESD in higher education, some university programs placed their emphasis on active learning and development of skills to solve problems that students would face in the real world [28][29][30]. The university's role in regional sustainability, on the other hand, includes educating citizens to foster volunteers who can contribute to developing sustainability in local communities [31] and developing partnerships for SD initiatives between universities and other local stakeholders [32], which have been manifested by efforts to set up Regional Centers of Expertise on ESD around the world [33,34]. Although not explicitly stated, those activities overlap with the engagement of scholarship.…”
Section: Universities' Roles In Education For Sustainable Developmentmentioning
confidence: 99%
“…In the present study, 68 federal universities were identified, offering 100 Business Administration programs on different campuses of Brazilian federal universities. These 100 programs are the basis of the research (Neuendorf, 2016).…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…In the previous study (Palma et al, 2011), the PPP or the curricular matrix was available for 40 of the 45 surveyed universities, representing 89% of all Business Administration programs offered. In the IJSHE 24,6 present study, from the 100 total programs surveyed at 68 federal universities, 90 PPPs or curricular matrices were found and considered for analysis (Neuendorf, 2016).…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…In addition to promoting multi-stakeholder participation the RCE also seeks to develop a platform for dialogue between NGOs, school teachers and administrators, and between environmental and educational administrations. Whereas several peer reviewed papers describing and advocating RCEs have been published (Mochizuki and Fadeeva 2008;Fadeeva and Mochizuki 2010;Ofei-Manu and Shimano 2012), there have, unfortunately, not been any critical reviews of the way the RCEs work and the extent to which the rhetoric of social learning is matched by concrete actions on the ground.…”
Section: Esd As Social Learning In the Context Of Local And Regional mentioning
confidence: 99%